MOTIVATION IN ANDREA HIRATA’S NOVEL THE RAINBOW TROOPS - Wahyu Fatahilla; M. Manugeren; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2020)
This research is concerned with the motivation in Andrea Hirata’s novel The Rainbow Troops. The novel is also a reflection of the biographical sketches of the author.  The objectives of the study are to identify the kinds of motivations reflected in The Rainbow Troops’ novel and to describe the motivations developing in “The Rainbow Troops” novel. Motivation is a direction and also energy for people to do everything included learning something. The researcher uses descriptive qualitative method in this study with the aim at describing a place, fact and characteristics of population systematically, factually and accurately. This research method is also appropriate to expose social phenomena.  The data are in the forms the text and quotation from the novel containing motivation. The results of research show that there are two kinds of motivations found in the novel: extrinsic and intrinsic motivations. Extrinsic motivation consists of never giving up and education and attitude needs to be learned; for intrinsic: hard work for education, and honesty.